A secondary injury prevention program may decrease contralateral anterior cruciate ligament injuries in female athletes: 2-year injury rates in the ACL-SPORTS randomized controlled trial - Johnson, J. L.; Capin, J. J.; Arundale, A. J. H.; Zarzycki, R.; Smith, A. H.; Snyder-Mackler, L. (Journal of Orthopaedic & Sports Physical Therapy, 2020)
Objective: To determine whether the addition of perturbation training to a secondary injury prevention program reduces the rate of second anterior cruciate ligament (ACL) injury compared to the prevention program alone. Design: Single-blinded randomized controlled trial. Methods: Thirty-nine female athletes who intended to return to cutting/pivoting sports were enrolled 3 to 9 months after primary anterior cruciate ligament reconstruction (ACLR). Athletes were randomized to receive a training program of either progressive strengthening, agility, plyometrics, and prevention (SAPP) (n = 20) or SAPP plus perturbation training (n = 19); each had 10 sessions over 5 weeks. Occurrence and side of second ACL injury were recorded for 2 years after primary ACLR. Results: There were 9 second ACL injuries in the 2 years after ACLR. There was no statistically significant difference in rate or side of second ACL injury between the SAPP-plus-perturbation training and SAPP groups. Conclusion: Adding perturbation training to a secondary ACL injury prevention program did not affect the rate of second ACL injury in female athletes.